2021
DOI: 10.3389/fphar.2021.716801
|View full text |Cite
|
Sign up to set email alerts
|

The Functions of Cytochrome P450 ω-hydroxylases and the Associated Eicosanoids in Inflammation-Related Diseases

Abstract: The cytochrome P450 (CYP) ω-hydroxylases are a subfamily of CYP enzymes. While CYPs are the main metabolic enzymes that mediate the oxidation reactions of many endogenous and exogenous compounds in the human body, CYP ω-hydroxylases mediate the metabolism of multiple fatty acids and their metabolites via the addition of a hydroxyl group to the ω- or (ω-1)-C atom of the substrates. The substrates of CYP ω-hydroxylases include but not limited to arachidonic acid, docosahexaenoic acid, eicosapentaenoic acid, epox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 124 publications
0
27
0
Order By: Relevance
“…157,158,[160][161][162][163] In particular, 20-hydroxyeicosatetraenoate has been shown to activate nuclear NF-κB, increase adhesion molecules, stimulate the production of inflammatory cytokines in endothelial cells, and promote vascular inflammation. 164 Both epoxyeicosatrienoates and hydroxyeicosatetraenoates have been implicated in SAH and explored as potential therapeutic targets. The level of 20-hydroxyeicosatetraenoates is increased in the CSF of humans and animals after SAH, which correlates with poor outcomes, and inhibitors of 20-hydroxyeicosatetraenoate synthesis prevent the acute and delayed changes in cerebral blood flow in experimental SAH.…”
Section: Inflammation In the Development Of DCImentioning
confidence: 99%
“…157,158,[160][161][162][163] In particular, 20-hydroxyeicosatetraenoate has been shown to activate nuclear NF-κB, increase adhesion molecules, stimulate the production of inflammatory cytokines in endothelial cells, and promote vascular inflammation. 164 Both epoxyeicosatrienoates and hydroxyeicosatetraenoates have been implicated in SAH and explored as potential therapeutic targets. The level of 20-hydroxyeicosatetraenoates is increased in the CSF of humans and animals after SAH, which correlates with poor outcomes, and inhibitors of 20-hydroxyeicosatetraenoate synthesis prevent the acute and delayed changes in cerebral blood flow in experimental SAH.…”
Section: Inflammation In the Development Of DCImentioning
confidence: 99%
“…Therefore, in this study, we first tested the ability of kurarinone to reduce neuroinflammation and improve behavioral deficits in a PD mice model induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). To understand how kurarinone decreases inflammation and because its treatment resulted in elevated levels of epoxyeicosatrienoic acids (EETs), endogenous signaling molecules that control inflammation ( 27 ), we used several biochemical methods to determine the molecular target of kurarinone. The interactions between kurarinone and soluble epoxide hydrolase, the main enzyme metabolizing EETs ( 28 ), were confirmed using enzyme kinetics and cocrystallization.…”
mentioning
confidence: 99%
“…Zhang et al [16] have demonstrated that PUFA played an important role in mitochondrial damage inducing RPE degeneration in BCD patients and suggested that adeno-associated virus 2 (AAV2)-mediated gene therapy may be used as the treatment of BCD. Furthermore, some FA metabolites are involved in anti-inflammation, immunoregulation and so on, so that the defections of CYP4V2 protein function may influence the signaling pathway and even influence other aspects [17][18] . Therefore, the mutations of the CYP4V2 gene may have broad influences, and we still need more detailed studies to clarify the mechanism of BCD.…”
Section: Discussionmentioning
confidence: 99%